Peritoneal dialysis in polycystic kidney disease patients - Hajar Benzouina; aziza guennoun; Naima ouzeddoun; Rabia Bayahia; Loubnna Benamar (RDPLF, 2020)
Introduction: Peritoneal dialysis (PD) in patients with polycystosis. Currently, it can be offered as a first-line treatment in these patients. The aim of our work is to analyse and compare the clinical and biological parameters, the evolution of residual renal function, technical survival and specific complications of PD in PKR subjects treated with PD compared to those without PKR and treated with the same supplementation technique.Patients and methods: Retrospective, observational study between July 2006 and October 2019 including 191 PD patients, 15 of whom had PKR.Results: The prevalence of PKR in PD is 8.9%. PKR is associated with a better quality of dialysis compared to the non-PKR group thanks to the persistence of RFR, it is also associated with a better technical (59 months versus 47 months) and patient (82 years versus 76 years) survival. Predictors of adequate dialysis are BMI <22 kg/m2 and persistence of residual renal function (RRF) after 3 years of PD. Hernias are more common in PKR patients (20%) but no predictive factors have been identified.Conclusion: PD can be offered as first-line therapy in PKR patients. A comparative study between PD and hemodialysis in PKR patients is necessary to demonstrate the value of PD in this population